Implementation of Security and Order of Regional Property by the South Sumatra Provincial Asset Management Agency - Arwin Novansyah; Raniasa Putra; Andries Leonardo (Mahesa Research Center, 2025)
This article aims to explore and analyze the implementation of security and control of regional assets in South Sumatra Province and to identify the causes of the obstacles faced. The problem is focused on the many assets of the South Sumatra Provincial Government that are not managed properly, are in dispute, use assets that are not in accordance with their use, and even assets whose whereabouts are unknown. To analyze this problem, this article uses the implementation theory of Van Meter and Van Horn. Data were collected through interviews, observations, and documentation and analyzed qualitatively. This study concludes that the implementation still faces various obstacles, such as less than optimal budget support, weak proof of ownership as a result of weak administration and documentation systems, lack of responsibility from some heads of Regional Apparatus Organizations for the management of Regional Assets, and public awareness regarding the management of regional assets still needs to be improved and former officials who use goods who still want to use Regional Assets that are not in accordance with applicable regulations. To overcome this, the Regional Government of South Sumatra Province needs to... provide training or workshops to OPD heads and their staff, allocate a special budget, including building an information system for regional asset management that can help overcome the weak evidence of asset ownership by the South Sumatra Provincial Government. If these obstacles have been overcome, it is not impossible to create effective asset management.